2014
DOI: 10.1371/journal.pone.0106912
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Phospholipid and Polyunsaturated Fatty Acid Composition in Diabetic Retinopathy

Abstract: BackgroundLong chain polyunsaturated fatty acids (LCPUFAs) including docosahexaenoic acid and arachidonic acid are suspected to play a key role in the pathogenesis of diabetes. LCPUFAs are known to be preferentially concentrated in specific phospholipids termed as plasmalogens. This study was aimed to highlight potential changes in the metabolism of phospholipids, and particularly plasmalogens, and LCPUFAs at various stages of diabetic retinopathy in humans.Methodology and Principal FindingsWe performed lipido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 38 publications
3
39
0
6
Order By: Relevance
“…4-Hydroxyalkenals are the most toxic products in lipid peroxidation and were found in the retina as early as 6 weeks of diabetes 75 . Our results was found to be in agreement with several studies on diabetes-induced changes in retinal fatty acid metabolism 76,77 that revealed a significant decrease in unsaturation level in diabetic retina. Lipid peroxidation serves as an indicator of the oxidative stress in diabetes mellitus 52 , and it occurs due to the abundance of unsaturated fatty acids in biological membranes that are mainly attacked by free radicals.…”
Section: Discussionsupporting
confidence: 93%
“…4-Hydroxyalkenals are the most toxic products in lipid peroxidation and were found in the retina as early as 6 weeks of diabetes 75 . Our results was found to be in agreement with several studies on diabetes-induced changes in retinal fatty acid metabolism 76,77 that revealed a significant decrease in unsaturation level in diabetic retina. Lipid peroxidation serves as an indicator of the oxidative stress in diabetes mellitus 52 , and it occurs due to the abundance of unsaturated fatty acids in biological membranes that are mainly attacked by free radicals.…”
Section: Discussionsupporting
confidence: 93%
“…Although farE is induced by and promotes resistance to linoleic acid, S. aureus would be exposed to a changing diversity and abundance of free fatty acids, dependent on the context within the human body. In a tissue abscess, pus contains high concentrations of unsaturated free fatty acids (UFFA), which could be derived from triglyceride (18,51) or human cell membrane phospholipid, where each of the major unsaturated fatty acids, oleic (C 18:1 ), linoleic (C 18:2 ), and arachidonic (C 20:4 ) acid, comprises approximately 13 to 15% of the total fatty acid content (22,23). Conversely, although sapienic acid or its isomer palmitoleic acid (C 16:1 ) do not comprise a major proportion of the fatty acid profile of phospholipid, sapienic acid is the major unsaturated fatty acid in human sebum, both as free fatty acid and in sebum triglyceride (14,52).…”
Section: Resultsmentioning
confidence: 99%
“…In other work, bactericidal assays conducted with human nasal secretions established that cholesterol esters of linoleic and arachidonic acids were the principal components with bactericidal activity toward Pseudomonas aeruginosa, which does not colonize the nose, but that they did not affect viability of S. aureus (16); linoleic acid is also the principal antimicrobial fatty acid in homogenates of murine tissue abscesses (18,51). Although arachidonic acid was not identified as a major fatty acid in abscess homogenates, it is a major unsaturated fatty acid in erythrocyte and leukocyte membrane phospholipid (23,70), from which it is released by phospholipases at sites of infection and rapidly converted to inflammatory mediators (71). Therefore, the induction of farE in response to linoleic and arachidonic acids may represent an evolutionary feature that contributes to the success of S. aureus as a human pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct trans-esterification of lipids can either be acid or base-catalyzed. Reagents commonly used for acid catalyzed trans-esterification are: methanolic hydrochloric and sulfuric acid [33]; and boron trifluoride in methanol [10,34,35] whereas reagents that have been used for base-catalyzed trans-esterification of biological samples are sodium methoxide [16,31] and potassium hydroxide in methanol [6]. Boron trifluoride in methanol (12-14%) is the most often used for transesterification of RBC lipids [26].…”
Section: Methylation Proceduresmentioning
confidence: 99%